PENGARUH CORPORATE GOVERNANCE DAN FIRM SIZE TERHADAP PERUSAHAAN YANG MENGALAMI KESULITAN KEUANGAN (FINANCIAL DISTRESS) - Sastriana, Dian; Fuad, Fuad (Diponegoro Journal of Accounting, 2013)
This study aimed to examine the effect of corporate governance and firm size for firms experiencing financial distress at non-financial companies. corporate governance used in this study is divided into five variables: the number of board of directors, the number of independent board, institutional ownership, managerial ownership, and the number of audit committee members. The other variable is firm size. This study also uses the control variables of leverage and liquidity. This study uses all firms are listed in the Indonesia Stock Exchange (IDX). The data obtained from the annual report and the Indonesian Capital Market Directory (ICMD) the period of 2009 to 2012. The data in 2009, 2010, and 2011 are used to predict financial distress at 1 year after the year of 2010, 2011, and 2012. The data were analyzed using logistic regression model. Results of this study showed that the variables that significantly influence the company experiencing financial distress only variable number of board of directors and the number of audit committee members. While the number of independent board variables, institutional ownership, managerial ownership and firm size do not have a significant influence on companies experiencing financial distress.